Phenomenon Shifting Mother Tongue in Indonesia (Global Scientific Review, 2023)
This study is motivated by the phenomenon of mother language shift in Indonesia. Therefore, this study aims to describe the causes of the phenomenon of mother language shift in Indonesia. This research method uses literature review. The research results show that the role of parents in the family and school is a factor causing the shift of regional languages as the mother tongue used by the current generation of speakers.